Lack of direct association between viral hepatitis and sleep disturbances - Lin, Sheng-Jie; Tang, Shang-Ching Joy; Lee, Yu-Chia; Liu, Ting-Yu; Huang, Ting-Chun; Yu, Rwei-Ling; Tan, Chun-Hsiang (Frontiers in Medicine, 2022)
Background Individuals with chronic viral hepatitis are at increased risk of experiencing poor sleep quality and sleep disturbances. However, it remains unclear whether the sleep disorders associated with viral hepatitis are secondary to the comorbidities related to viral hepatitis or the direct effect of hepatitis viruses on sleep. This study investigated the direct impact of viral hepatitis B and C on sleep quality. Methods Individuals with viral hepatitis B or C and their healthy counterparts were recruited for the present study, and they were evaluated with the Parkinson's Disease Sleep Scale-2, the Epworth Sleepiness Scale, and the Pittsburgh Sleep Quality Index in the absence of common comorbidities associated with viral hepatitis. Results Neither hepatitis B nor hepatitis C was found to cause significant differences in insomnia symptoms or excessive daytime sleepiness. However, individuals with hepatitis C, but not hepatitis B, tended to be less likely to experience restlessness of the legs or arms at night. Conclusions This study suggests that hepatitis viruses B and C may not cause a significant impact on sleep quality and related disorders directly. Sleep disturbances in individuals with chronic viral hepatitis may instead be attributable to hepatic decompensation or the comorbid factors associated with viral hepatitis.